1995
DOI: 10.6028/jres.100.050
|View full text |Cite
|
Sign up to set email alerts
|

Precision tests of quantum hall effect device DC equivalent circuit using double-series and triple-series connections

Abstract: Precision tests verify the dc equivalent circuit used by Ricketts and Kemeny to describe a quantum Hall effect device in terms of electrical circuit elements. The tests employ the use of cryogenic current comparators and the double-series and triple-series connection techniques of Delahaye. Verification of the dc equivalent circuit in double-series and triple-series connections is a necessary step in developing the ac quantum Hall effect as an intrinsic standard of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…However, when nonadjacent terminals are short-circuited together, the resulting resistance value can be a multiple or a fraction of R H . Fang [6, figure 1(a DC analytical modelling of double-and triple-series connections of single and twin devices was performed in [2] and [3]; in [5] the analysis was extended to the ac regime. The modelling process is based on the Ricketts-Kemeny model [7] of the quantum Hall device, or on its derived ones [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when nonadjacent terminals are short-circuited together, the resulting resistance value can be a multiple or a fraction of R H . Fang [6, figure 1(a DC analytical modelling of double-and triple-series connections of single and twin devices was performed in [2] and [3]; in [5] the analysis was extended to the ac regime. The modelling process is based on the Ricketts-Kemeny model [7] of the quantum Hall device, or on its derived ones [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…In this section we analyse the effect of contact resistances on several examples of single device connections (table 1, first column). These examples, which were already analysed using other methods by Delahaye[2] and by Jeffery et al[3], have been chosen for their practical interest. For each connection, the second column of table 1 shows a suitable choice of port voltages and the third column shows the corresponding matrix A.…”
mentioning
confidence: 99%
“…The two-terminal resistance of this device connection differs from R H by a relative error of order (R C /R H ) M where M is the number of external leads connected to discrete high or low device contacts. 20,21 For M = 3, R C ≤ 10 , and R H = R K /2, the resulting resistance value differs from the conventional four-terminal QHR resistance value by less than one part in 10 9 .…”
Section: Minimizing Qhr Lead Resistance Errormentioning
confidence: 96%
“…Therefore the indirectly measured acl/12.9QFI quadratic dependence is (-1.3 ± 1.4) x 10W81kHz2. Equivalent Circuit Model Jeffery, Etmquist, and Cage [4] showed that the Ricketts and Kemeny equivalent electrical circuit model [5] represents multi-series-connected dc QHR devices to 1 part in 109 accuracies. That Ricketts/Kemeny model [5] lies at the heart of the Cage/Jeffery/Matthews equivalent electrical circuit representation [3] of an ac QHR standard with two external quadruple-series connections when measured under 4TP balance conditions.…”
Section: Exderimentmentioning
confidence: 99%